Seleksi dan Karakter Sekunder Jagung Inbrida Toleran Cekaman Kekeringan - Badaruddin, Muhammad Farid; Efendi, Roy; Nur, Amin; Azrai, dan Muhammad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
The availability of drought-tolerant maize inbred materials are useful to develop a hybrid or synthetic drought tolerant maize varieties. This research was aimed to select drought tolerant and determine secondary traits for selection of inbred maize. Selection of 31 maize inbred lines was conducted in nested experimental design in which the replicate was nested into the drought stress selection condition and normal irrigation. Drought stress treatment was applied during flowering to milk phase. In the normal irrigation condition the water was supplied every 10 days. The results showed that the medium tolerant to tolerant to drought stress inbred lines were 1044-30, DTPYC9-F46-3-9-1-1-B, CML161 / NEI9008, DTPYC9-F46-1-2-1-2- B, and Mr14. The yield declined of tolerant/medium tolerant inbred lines of about 17.0-38.3% was lower than sensitive inbred lines of about 42.8-70.7% under stress condition. The tolerant/medium tolerant inbred lines can be used for developing drought tolerant or synthetic varieties. The secondary traits effective for selection of drought tolerant inbred lines were shelling percentage, leaf chlorophyll, leaf rolling scores, number of tassel, the female flowering dates, and anthesis silking interval (ASI). The traits were more effected by genetic factors than the environmental factors and correlated to yield under drought stress conditions.Keywords: anthesis silking interval, environmental condition, inbred lines, tassel number, yield